Learning outcomes in online citizen science communities designed for inquiry. Issue 4 (1st October 2020) - Aristeidou, Maria; Scanlon, Eileen; Sharples, Mike
ABSTRACT: The purpose of most citizen science projects is engaging citizens in providing data to scientists, not supporting citizen learning about science. Any citizen learning that does occur in most projects is normally a by-product of the project rather than a stated aim.This study examines learning outcomes of citizens participating in online citizen science communities purposely designed for inquiry learning. The 'Citizen inquiry' approach adopted in this study prioritises and scaffolds learning and engages people in all stages of the scientific process by involving them in inquiry-based learning while participating in citizen science activities. The exploratory research involved an intervention with two design studies of adult volunteer participants engaging in citizen-led inquiries, employing a mixed-methods approach. The findings indicated that, in both design studies, participants engaged in an inquiry process, and practised inquiry skills alongside other kinds of knowledge and skills not directly related to science. Differences between the outcomes of each study highlighted the importance of the design on learning impact. In particular, participant understanding of research processes and methods, and developing more experimental studies were more evident with the support of a dynamic representation of the inquiry process. Furthermore, in the second study, which was hosted in a more engaging and interactive learning environment, participants perceived science as fun, were involved in inquiry discussions, and showed progress in scientific vocabulary. The paper concludes with some considerations for science educators and citizen science facilitators to enhance the learning outcomes of citizen inquiry and similar online communities for science inquiries.